Siah-1b is a direct transcriptional target of p53: Identification of the functional p53 responsive element in the siah-1b promoter - Fiucci, Giusy (National Academy of Sciences, 2004)
Siah proteins are E3 ubiquitin ligases. They are homologues of the Drosophila seven in absentia (Sina), a protein required for the R7 photoreceptor development. We have previously found that the expression of human siah-1 and its mouse homologue siah-1b are induced by p53 during apoptosis and tumor reversion. So far, no evidence that the siah-1b gene is a direct transcriptional target of p53 has been provided. In the present study we investigate this issue. Northern blot analysis with a specific probe demonstrates an increase in siah-1b transcription on activation of endogenous and inducible exogenous p53. To explore whether this effect is directly mediated by p53 we analyzed 20 kb of chromosome X DNA, containing the siah-1b locus. A p53-binding site was identified in the siah-1b promoter, located at nucleotides -2155/-2103 relative to the translational start site. This site is composed of two half-sites, conforming to the p53-binding consensus sequence but separated by a nonclassical 33-bp spacer. In luciferase assays, p53 induces a substantial increase in siah-1b promoter activity. Gel shift and DNase-I-footprinting studies, combined with mutational analysis and chromatin immunoprecipitation, indicate that p53 effectively binds the siah-1b promoter in vitro and in vivo. Thus, the siah-1b gene is a direct transcriptional target of p53.